Microplastic exposure induces hepatotoxicity through oxidative stress: an investigation into the molecular mechanism - Bristow, Paolo Timothy (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.